2021
DOI: 10.3390/plants10050907
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Agronomic Practices on the Severity of Sweet Basil Downy Mildew (Peronospora belbahrii)

Abstract: Downy mildew (caused by Peronospora belbahrii) is a severe disease of sweet basil (Ocimum basilicum) crops around the world. We examined cultural methods for reducing the severity of sweet basil downy mildew (SBDM) under commercial conditions in greenhouses and walk-in tunnels. The effects of the orientation of walk-in tunnels, air circulation in greenhouses, plant density, and soil mulch were tested. SBDM was less severe in the tunnels that were oriented north-south than in those oriented east-west, but the y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
7
1
Order By: Relevance
“…In this study, a low nitrite content was found in low-density treatment, which is beneficial for the consumption of cucumber. Chen Omer also confirmed that a proper low plant density reduced the severity of sweet basil downy mildew, which may be also an important means of improving plant yield and quality [46]. Therefore, the cultivation density can be appropriately reduced to synthesize more chlorophyll in cucumber fruit peel and accumulate more metabolic substances, which not only helps to improve the taste of fruit but also meets consumer needs.…”
Section: Discussionmentioning
confidence: 81%
“…In this study, a low nitrite content was found in low-density treatment, which is beneficial for the consumption of cucumber. Chen Omer also confirmed that a proper low plant density reduced the severity of sweet basil downy mildew, which may be also an important means of improving plant yield and quality [46]. Therefore, the cultivation density can be appropriately reduced to synthesize more chlorophyll in cucumber fruit peel and accumulate more metabolic substances, which not only helps to improve the taste of fruit but also meets consumer needs.…”
Section: Discussionmentioning
confidence: 81%
“…In addition, although the densities of 45 × 20 cm and 30 × 30 cm had different distances within and between rows, their planting areas were the same (900 cm 2 ). In other studies, it was reported that closer spacing also impedes proper air circulation between plants, leading to increased humidity and potentially promoting the occurrence of diseases [27,28]. With limited resources and space, plants might adopt a more energy-efficient strategy.…”
Section: Pgi Shoot Number Shoot Fresh Weight and Shoot Dry Weightmentioning
confidence: 99%
“…Reduced pollen-to-silking interval and increased harvest index, reflecting the partitioning of assimilates to the ear and grain, have been suggested as indicators of tolerance to drought (Duvick, 2005 ; Lopes et al, 2011 ). Crops grown at low populations are less susceptible to damage due to frost (Whaley et al, 2004 ), diseases (Jurke and Fernando, 2008 ; Farias et al, 2019 ; Omer et al, 2021 ), and lodging (Jurke and Fernando, 2008 ; Chauhan et al, 2021 ). The potential offset from the reduced population of lower seed cost is remarkable because seed represents one of the essential economic inputs (Spink et al, 2000 ); reasonably minimized seed waste might be significant concerning food adequacy and security in the future (Tokatlidis, 2014 ).…”
Section: Benefits From the Productive Ideotypementioning
confidence: 99%